The synthesis and study of novel ferrocenyl-benzimidazole derivatives as antiplasmodial agents - Ndlovu, Malcolm Thabo (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.